Lessons learned from developing a statewide research data repository to combat the opioid epidemic in Alabama. Issue 3 (1st August 2022) - Hudnall, Matthew; Lewis, Dwight; Parton, Jason; Sellers, Christopher
Abstract: Many states are continuing to struggle with opioids and other commonly abused drugs. Alabama, being the highest opioid prescription per-capita state since 2012, has pulled together state agencies, private companies, academia, and community organizations to form a data council and repository to provide unified insights and information to the public and partner stakeholders. The lessons learned in constructing this data environment are documented so that other states and organizations can benefit from the challenges and success that Alabama has experienced. The centralized data repository consists of almost a dozen data streams from public agencies and private companies. The data are transformed and linked within the repository to provide geo-temporal linkages between data sources. The data are stored in a secure multi-tiered environment in a Microsoft SQL Server database, de-identified, aggregated, and then published to a public web portal for open consumption. The public-facing website from the project successfully integrates multiple disparate data sources into a common platform for streamlined and cohesive data communications. Drug addiction cannot be easily quantified, viewed, or otherwise examined when only looking at a portion of society. By bringing together multiple data sources and linking them, a more clear picture of trends, influences, and metrics can be obtained. A statewide drug use data partnership between public and private entities is both possible as well as beneficial to all parties involved. Items like legal contracts can inhibit data sharing, but certain best practices can help scale and streamline multiple agreements. Lay Summary: As state and federal policies have facilitated a downward trend in the abuse and misuse of prescription opioids, the incidence of deaths due to illicit synthetic opioids perpetuates the well-documented public health challenge of opioids in the United States. The transient nature of America's opioid epidemic produces the demand for timely data from multiple sources to mitigate this multi-faceted problem. Moreover, many state government agencies experience challenges in recruiting and retaining personnel with the needed advanced analytic skillsets to promote effective planning management strategies to combat the opioid epidemic. So analytic support from neighboring universities could address this human capital challenge. The purpose of this case report is to highlight activities in developing Alabama's Drug Use Centralized Data Repository (DrugUse-CDR). More specifically, we will highlight (1) the origins of DrugUse-CDR, (2) the academic–government collaboration in DrugUse-CDR, (3) the success and challenges of DrugUse-CDR, and (4) the next steps of the program.